Essential role of Notch4/STAT3 signaling in epithelial–mesenchymal transition of tamoxifen-resistant human breast cancer. (1st April 2017) - Bui, Quyen Thu; Im, Ji Hye; Jeong, Sung Baek; Kim, Young-Mi; Lim, Sung Chul; Kim, Bumseok; Kang, Keon Wook
Abstract: We previously demonstrated that tamoxifen (TAM)-resistant human breast cancer (TAMR-MCF-7) cells showed increased expression of mesenchymal marker proteins compared to the parent MCF-7 cells. Notch is functionally important in the promotion of epithelial–mesenchymal transition (EMT) during both development and tumor progression. Notch1 and Notch4 have been reported as prognostic markers in human breast cancer. Here, we indicated that Notch4, but not Notch1, plays a critical role in the regulation of EMT signaling in TAMR-MCF-7 cells. Notch4 suppression by either Notch inhibitors or Notch4 siRNA attenuated EMT signaling. Tyrosine-phosphorylated STAT3 protein is known as a crucial signaling molecule in the regulation of tumorigenesis and metastasis. We found that TAMR-MCF-7 cells exhibited constitutive STAT3 phosphorylation, and Notch inhibition reduced the level of activated STAT3 in TAMR-MCF-7 cells. An intrasplenic injection model of liver metastases was performed using TAMR-MCF-7 cells. Mice injected with N-[N-(3, 5-Difluorophenacetyl)-l -alanyl]-S-phenylglycine t-butyl ester (DAPT, 10 mg/kg) formed smaller splenic tumors and showed a reduced micrometastatic tumor burden in their livers compared with the control group treated with vehicle. To conclude, Notch4 could be a potential target to prevent metastasis in TAM-resistant breast cancer. Highlights: Notch4 plays a critical role in EMT signaling in tamoxifen-resistant breast cancer. Notch4/STAT3 crosstalk is important for EMT. Notch inhibition suppresses the micrometastatic tumor burden.